Validity of critical speed and a simple ranking method as a predictor of triathlon performance outcome - Smith, C.
Since performing at an individual`s AT or CS determines the extent of their ability to exercise for a long time without fatigue CS can be used to predict an individual`s performance. The first part of this study validates CS as a method for predicting performance in each subdiscipline of a triathlon event (swim, bike, and run). The second part of this study applies CS with a simple ranking method to determine triathlon outcome at a triathlon event. Results significantly show that CS can statistically predict individual performance in the swim, bike, and run separately. Results also show that a simple method of ranking CS results for an individual predicts the outcome of a triathlon race.